'Don't just look for a new pet': the Vietnamese airlift, child refugees and the dangers of toxic humanitarianism1. (27th May 2018) - Taylor, Becky
ABSTRACT: The Kindertransport remains the most common historical point of reference in contemporary debates over the present position of refugees in Europe. Taylor's article instead focuses on a very different emergency movement of children—the airlift of ninety-nine 'orphans' from Vietnam before the fall of Saigon in April 1975—as a historical point of entry into Britain's relationship with child refugees. Although superficially a one-off event, and an example of 'toxic' humanitarianism, in fact it is suggestive of some of the key themes of modern refugee history. These include the tendency of humanitarianism to hollow out political contexts from the objects of their concern; the prominent, and sometimes problematic, role of voluntary organizations in the movement, reception and resettlement of refugees; and the place of expressions of spontaneous compassion by individuals who become involved in refugee operations. Taylor's article suggests that all these themes could fruitfully bear greater historical attention.